Integrating Education, Research, and Service: A Participatory Action Research (PAR) Model for University-Led Community Empowerment in Rural Indonesia - Sulis Sriani Putri; Nur Fauziah Purba; Tamara Dilla Tiffani; Anjas Juliansyah Siregar; Moh Iqbal Abdul Muin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study examines the implementation of the Tri Dharma of Higher Education through the Community Service Program (KKN) of the State Islamic University of North Sumatra in Bahbutong I Village, Simalungun Regency, using a Participatory Action Research (PAR) approach. The program focuses on sustainable community empowerment by positioning students as partners who collaborate with residents in identifying potential, formulating solutions, and implementing real programs. Research data were obtained through observation, interviews, focus group discussions, participatory documentation, and joint evaluation. The results indicate that the KKN activities successfully integrated the aspects of education, research, and community service. In terms of education, students play a role in enhancing literacy, health awareness, and strengthening religious values through the teaching of fardhu kifayah. In terms of research, village potential mapping is conducted to reveal opportunities for the development of micro, small, and medium enterprises (MSMEs) as well as various challenges faced by the community. Meanwhile, in terms of service, students implement concrete programs such as providing waste management facilities, organizing MSME bazaars, and village festivals that promote economic growth, cultural preservation, and social solidarity. Overall, these findings affirm that PAR-based community service not only enriches students’ learning experiences but also provides tangible benefits to village communities, while serving as a strategic model for other universities to sustainably optimize the Tri Dharma.